Advances in taxation. Volume 24 - Hasseldine, John (Emerald Publishing Limited, 2017)
Volume 24 of Advances in Taxation contains seven articles, covering topics such as the impact of FASB Financial Interpretation No. 48 adoption through the lens of debt covenants; conflicting results in two prior studies on the relation between aggressive financial reporting and tax reporting; how a firm's external environment affects its tax avoidance activities; and bonus depreciation. Other articles use a behavioral research methodology to explore generational values and attitudes towards tax fairness and tax compliance; the expectation gap between tax clients' motivations to hire tax preparers versus tax preparers' perceptions of those clients' motivations; and evidence on the level and determinants of corporate income tax compliance costs.- Resumé vydavatel
Obsahuje index.
Keywords: daně -- Spojené státy americké; daně -- Řecko; taxation -- United States; taxation -- Greece; sborníky; elektronické knihy; papers of several authors; electronic books